2022
DOI: 10.3390/su14148620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Matrix Dam in the Paddy Field Drainage Ditch on Water Purification Based on the Physical Model Test

Abstract: (1) Setting a matrix dam in the paddy field drainage ditch has been recognized as an effective method to lower the velocity of water discharged from a paddy field in the drainage ditch, which can improve the purification efficiency of the drainage ditch for nitrogen and phosphorus pollutants, but the specific placement and thickness of the matrix dam have not been supported due to the insufficient research results. (2) Three thicknesses of the matrix dam were set in three locations of the physical model of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…There are many experimental studies and model simulations on the purification effects, processes, and degradation mechanisms of pollutants in agricultural drains [21][22][23]; for example, Kroger [24,25] found that a 400 m long and 7 m wide agricultural ditch could retain 57% of soluble inorganic nitrogen. Fan et al [26] developed a nitrogen balance model by analyzing the changes in TN, NH 4 + -N, and NO 3 − -N content in the whole system, providing a new idea for enhanced nitrogen removal from drainage ditch systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are many experimental studies and model simulations on the purification effects, processes, and degradation mechanisms of pollutants in agricultural drains [21][22][23]; for example, Kroger [24,25] found that a 400 m long and 7 m wide agricultural ditch could retain 57% of soluble inorganic nitrogen. Fan et al [26] developed a nitrogen balance model by analyzing the changes in TN, NH 4 + -N, and NO 3 − -N content in the whole system, providing a new idea for enhanced nitrogen removal from drainage ditch systems.…”
Section: Introductionmentioning
confidence: 99%